Analysis The Effect Of Production Costs, Operational Costs And Sales Volume On Net Profit (Study On Cosmetic & Household Subsector Companies Listed On The Indonesia Stock Exchange In 2017-2021) - Suzan, Leny; Febrianti Siagian, Hosanna Alicia (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Success indicators of the company's performance are generally measured based on how much net profit is earned. To get the expected profit, profit planning must be carried out to predict the company's condition in the future, as well as to monitor the opportunities for factors that can affect profits. This study aims to analyze the effect of production costs, operating costs, and sales volume on the net income of cosmetic companies listed on the Indonesia Stock Exchange (IDX), either simultaneously or partially. Collecting data in this study using a purposive sampling method. This research uses objects of cosmetic manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The population in the study totaled 12 companies but only 6 selected samples met the criteria. The analysis technique used in this research is panel data regression analysis with data processing using Eviews version 12. The results obtained from this study are that simultaneously production costs, operating costs and sales volume significantly affect net income. The adjusted R-squared value obtained at the coefficient of determination of 0.984828 (98.48%) indicates production costs, operational costs, and sales volume can explain net income and the remaining 1.52% is explained by variables outside this study. Partially, production costs and operational costs have a negative effect on net income, and sales volume has a positive effect on net income.